2006
DOI: 10.1152/ajplung.00178.2005
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of CFTR to apical-basolateral fluid transport in cultured human alveolar epithelial type II cells

Abstract: Previous studies in intact lung suggest that CFTR may play a role in cAMP-regulated fluid transport from the distal air spaces of the lung. However, the potential contribution of different epithelial cells (alveolar epithelial type I, type II, or bronchial epithelial cells) to CFTR-regulated fluid transport is unknown. In this study we determined whether the CFTR gene is expressed in human lung alveolar epithelial type II (AT II) cells and whether the CFTR chloride channel contributes to cAMP-regulated fluid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
138
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(153 citation statements)
references
References 44 publications
12
138
1
Order By: Relevance
“…2A). This finding is essentially in line with the proposed facilitation of alveolar fluid clearance by Cl − uptake under physiological conditions (10). Conversely, Cl − -free lung perfusion selectively inhibited secretory fluid transport at elevated P LA (Fig.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…2A). This finding is essentially in line with the proposed facilitation of alveolar fluid clearance by Cl − uptake under physiological conditions (10). Conversely, Cl − -free lung perfusion selectively inhibited secretory fluid transport at elevated P LA (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Depending on the actual electrochemical gradient, CFTR expressed in the apical plasma membrane can mediate both Cl − absorption and secretion by alveolar epithelial cells (10). We, therefore, tested whether alveolar secretion of Cl − and fluid at hydrostatic stress requires CFTR.…”
Section: Resultsmentioning
confidence: 99%
“…Lungs were obtained from five adult males without lung disease who died after head trauma or cerebrovascular accident. Type II cells were isolated by our published methods (18,19). Freshly isolated human AT II cells were plated in the upper compartment of Transwells (0.4-mm pore size and collagen I coated; Costar, Corning) in DMEM-H21 and F-12 Ham's (1:1) plus 10% FBS.…”
Section: Primary Cultures Of Human At II Cellsmentioning
confidence: 99%
“…Although we have shown that TGF-␤1 inhibits basal and corticosteroid-stimulated alveolar fluid transport (22), the potential effect of TGF-␤1 on the ␤-adrenergic-stimulated alveolar fluid transport is still unknown. Recent experimental evidence convincingly demonstrated in mice and humans a role for the cystic fibrosis transmembrane conductance regulator (CFTR) in the ␤ 2 AR agonist-mediated stimulation of the alveolar epithelial fluid transport (23)(24)(25)(26)(27)(28)(29). Thus, the objective of this study was to examine the mechanisms by which TGF-␤1 would inhibit the ␤ 2 AR agonist-stimulated CFTR-dependent alveolar epithelial fluid transport.…”
Section: Acute Lung Injury (Ali)mentioning
confidence: 99%